Visual Communication in Opening Bumper Break Motion Graphic Design (Case Study at the International Conference on Safe Communities Event at Mahardhika Creative) - Muhammad Ihza Bani; M Denu Poyo; Hanindyalaila Pienrasmi (Indonesian Journal Publisher, 2025)
This research discusses the visual communication involved in the International Conference on Safe Communities event at Mahardhika Creative. The problem raised in this research is how to visual communication in the Motion Graphic Opening Bumper Break (OBB) at the International Conference on Safe Communities at Mahardhika Creative. This research was conducted to find out more about the relationship and role of visual communication in the design of opening bumper break Motion Graphic. This research was conducted using a qualitative approach method. By using this approach, we are able to describe and describe the phenomena that occurred among Mahardhika Creative employees at the International Conference on Safe Communities event. This research was conducted in February 2025. Data collection was carried out by observation and interviews with informants who met the requirements for this research. The results that will be obtained in this research are the event background, the function of Motion Graphic and the opening bumper break in an event